Institutionalising decarbonisation in South Africa: navigating climate mitigation and socio-economic transformation. (20th October 2021) - Tyler, Emily; Hochstetler, Kathryn
ABSTRACT: Strong climate institutional governance is necessary for countries to meet their international climate mitigation commitments. This article shows that while South Africa steadily created climate institutions up to 2011, these failed to take hold in the following years. Also, despite the systemically critical energy sector dominating the emissions profile, these climate institutions had no purchase over it. This situation is largely due to South Africa's political economy of energy, which gave powerful actors the sustained ability to block meaningful institutionalisation of decarbonisation in the energy sector. As a result, South Africa's climate institutions play few of the roles expected for successful institutionalization of climate action, with energy institutions instead playing a shadow climate governance role. This case suggests that conceptions of climate institutional governance in countries where single sectors dominate in emissions and power must accommodate the roles of institutions affecting climate outcomes despite this not being their primary objective.